Experimental and computational investigation of sound absorption performance of sustainable porous material: Yucca Gloriosa fiber. (1st January 2020) - Soltani, Parham; Taban, Ebrahim; Faridan, Mohammad; Samaei, Seyed Ehsan; Amininasab, Somayeh
Highlights: Sound absorption coefficients of the samples made of Yucca fibers were studied. Yucca fibers effectively dissipate energy of sound wave and enjoy high absorption. The effects of sample thickness and airgap behind the samples were investigated. A computational method for prediction of sound absorption coefficient was proposed. Predicted absorption coefficients have a good agreement with the measured data. Abstract: The aim of this study is to provide a better comprehension and predict acoustic behavior of Yucca Gloriosa (YG) fiber using experimental and computational approaches. To this end, the FESEM images of fibrous samples with thickness of 15 and 30 mm were obtained and fiber diameter and orientation distribution were calculated using image analysis techniques. An in house Matlab-based code capable of generating fibrous structures was developed. The obtained parameters from experimental and morphological analysis of samples were implemented into the code to simulate 3D virtual structure of samples. Flow resistivity and tortuosity were calculated by numerically solving Stokes flow and Fick's law through the 3D void space of generated structures, respectively. Different models able to predict the acoustic impedance and frequency-dependent sound absorption coefficient (SAC) of porous materials, including Delany and Bazley (D-B), Garai and Pompoli (G-P) and Johnson-Champoux-Allard (JCA) were analyzed and their suitability for prediction of acoustic behavior of YG fibers was evaluated. The results were compared with experimental data obtained using impedance tube method. It was concluded that at frequency range of 63–6300 Hz, the JCA model has superior predictive ability compared to D-B and G-P models and is well suited to YG fibers. It was found that the peak of SAC for samples with thickness of 15 and 30 mm emerges at 4000 and 2500 Hz, respectively. It was established that, YG fibrous samples effectively dissipate the energy of sound waves. This was attributed to the longer depreciation process of thermal and viscous transfer between the air and the absorbing media.